Dah Dzāhge Nodesidē/We Are Speaking Our Language Again: The Implementation of a Community-Based Tāłtān Language Reclamation Framework (KULA, 2021)
As a member of the Tahltan Nation, I carried out research that centred on community experiences of language reclamation. The investigation focused on how language reclamation is connected to health and healing, as well as what has been done and what still needs to be done to revitalize and reclaim the Tahltan language. Language reclamation is the start of a process in which our people heal from the impacts of colonization and assimilation by reclaiming our language, culture, and identity, thereby allowing our voices to become stronger and healthier. From what was learned from community co-researchers, scholars who have worked with our communities, Indigenous community language revitalization experts, and international language revitalization scholars, I developed a Tāłtān Language Reclamation Framework focusing on governance; language programming; documentation; training and professional development; and resiliency, healing, and well-being. This report will discuss the ways in which this framework has been implemented in community over the last decade, highlighting examples such as the formation of a language governing body, Dah Dẕāhge Nodeside (Tahltan Language Reclamation Council); the implementation of language nests; the development of a Tāłtān language school K–8 curriculum; the creation of learning materials based on old and new recordings of first language speakers (e.g., digital apps and videos, websites, alphabet book, grammar resources); post-secondary fluency/proficiency community programming; and documentation training. Finally, we continue to focus on the relationship between language reclamation, intergenerational trauma, and healing, resiliency, and well-being. This will be done through community-based immersive programming that focuses on the nurturing of relationships with first language speakers in order to create not only learning resources, but safe and supportive environments for all speakersーlearners, second language speakers, silent speakers, and first language speakers.